Система математичних моделей для дослідження перспектив функціонування і розвитку газової галузі в сучасних умовах - Leshchenko I.Ch. (General Energy Institute of the National Academy of Sciences of Ukraine, 2017)
To study the prospects of development of the gas industry, we propose a system of mathematical models that takes into account the considerable uncertainties of external and internal conditions of its operation, the life time of main technological equipment, and constraints on investment resources. The optimization mathematical model of development of the gas industry is implemented in the modeling language MathProg, which enables one to describe the logic of mathematical model fairly transparently by using binary variables, which is quite problematic in the application of other optimizers. It is established that the use of GLPK optimizer enables one to solve large-scale problems with binary variables, which include the task of forecasting the functioning and development of gas industry within an acceptable time framework.